Traffic Violation Handling Against Children by The Police in The Jurisdiction of Badung Police - Arjaya, I Made; Sahadewa, Anak Agung Gede Ananta Wijaya; Ramadika, I Ketut Gede Adi; Wijaya, I Ketut Kasta Arya (Jurnal Pendidikan dan Pengajaran, 2025)
Introduction and learning of traffic orders is not only the responsibility of the police but also requires an active role from all parties to minimize the occurrence of traffic violations. The purpose of this study is to analyze the effectiveness of the implementation of traffic violation prevention against children. This type of research is qualitative. The population in this study includes all police officers, and the sample was determined purposively. The data collection method combines in-depth interviews, participatory observation, and documentation with instruments like interview guidelines, observation sheets, and documentation checklists. The data obtained were analyzed using qualitative descriptive analysis methods. The results of this study are that the duties and functions of the police in handling traffic violations by children have positively contributed to reducing the number of violations. A comprehensive approach involving various parties is the key to overcoming the problem of traffic violations by children. It is concluded that efforts to overcome traffic violations against children carried out by the Badung Police have gone in the right direction and have had a positive impact on increasing legal awareness among children. However, its effectiveness has not been maximized due to various supporting factors that are still limited. The implication is that there is a need to strengthen the synergy between the police, schools, and families in building legal awareness from an early age, as well as increasing institutional capacity in carrying out the functions of fostering and enforcing the law in a preventive and educational manner towards children.